2020
DOI: 10.1186/s13584-020-00367-4
|View full text |Cite
|
Sign up to set email alerts
|

Low intake of iodized salt and iodine containing supplements among pregnant women with apparently insufficient iodine status - time to change policy?

Abstract: Background: Iodine is an essential nutrient for human health throughout the life cycle, especially during early stages of intrauterine life and infancy, to ensure adequate neurocognitive development. The growing global reliance on desalinated iodine-diluted water raises the specter of increased iodine deficiency in several regions. The case of Israel may be instructive for exploring the link between iodine status and habitual iodine intake in the setting of extensive national reliance on desalinated water. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…Последствия ЙДЗ включают в себя как мертворождения, самопроизвольные аборты, возникновение врожденных аномалий у плода при тяжелом ЙД, репродуктивные нарушения, так и специфические заболевания щитовидной железы (ЩЖ), такие как гипотиреоз в районах с тяжелым ЙД и тиреотоксикоз, функциональная автономия (токсический узловой, многоузловой зоб) на территории с умеренным и легкой степени тяжести ЙД. Кроме того, хронический ЙД приводит к развитию умственной и физической отсталости детей, кретинизму, а также существенно увеличивает риск радиационно-индуцированного рака ЩЖ в случае ядерных катастроф [ 2 ][ 3 ].…”
Section: обоснованиеunclassified
See 1 more Smart Citation
“…Последствия ЙДЗ включают в себя как мертворождения, самопроизвольные аборты, возникновение врожденных аномалий у плода при тяжелом ЙД, репродуктивные нарушения, так и специфические заболевания щитовидной железы (ЩЖ), такие как гипотиреоз в районах с тяжелым ЙД и тиреотоксикоз, функциональная автономия (токсический узловой, многоузловой зоб) на территории с умеренным и легкой степени тяжести ЙД. Кроме того, хронический ЙД приводит к развитию умственной и физической отсталости детей, кретинизму, а также существенно увеличивает риск радиационно-индуцированного рака ЩЖ в случае ядерных катастроф [ 2 ][ 3 ].…”
Section: обоснованиеunclassified
“…Другие страны, не имеющие законодательного регулирования проблемы ЙД, также сообщают о необходимости его введения [ 22 ].…”
Section: обсуждение основного результата исследованияunclassified
“…A recent IJHPR article by Rosen and colleagues [10] has evaluated iodine status in 134 pregnant women living in an area reliant on desalinated iodine-diluted water. While iodine concentration in water from Ashkelon was 35 μg/L the water iodine concentrations in several municipalities in the Ashkelon subdistrict ranged between 0 and 9 μg/L.…”
Section: The Israel Situationmentioning
confidence: 99%
“…Mean urine iodine levels of school-aged children and pregnant women indicated that these populations were iodine-deficient [ 11 ]. Additional studies in recent years in Israel showed low iodine intake and low prevalence of iodized salt intake in pregnant women [ 12 ]. Previous research has shown that while Israeli milk and dairy products are iodine rich, consumption patterns of milk, dairy, as well as dairy-based foods, among Israeli adults do not ensure adequate iodine intake [ 13 ].…”
Section: Introductionmentioning
confidence: 99%